THE ROLE OF MARKETING IN THE CAR TIRE MARKET: STRATEGIES AND EFFECTIVENESS OF ADVERTISING CAMPAIGNS - Галина (THE INNOVATION ECONOMY, 2026)
The text of this work reveals the essence of the study of the impact of marketing activities on the market promotion of car tires in terms of analyzing key product promotion strategies and evaluating their effectiveness. The main focus of the work is on modern digital tools and the most effective advertising campaigns, which allow us to understand the mechanisms of the impact of marketing activities on demand and sales levels. The article provides a detailed description of the promising concepts of the leading global players in the car tire market through the lens of their inclusion in marketing programs. The article also explores the concept of the digital marketing funnel and presents the parameters of its interpretation in the implementation of car tires. The efficiency parameters of tire promotion channels have been analyzed based on various methods, as well as the cost level and expected level of efficiency.